Intra-industry competition among employer associations: a case study of the retail sector. (2nd April 2016) - You, Kevin; Barry, Michael
ABSTRACT: There is sizeable literature on how trade unions have responded to structural changes in the labour market and the re-regulation of labour laws in Australia. In comparison, however, there is little coverage on the responses of employer associations – even though they face many of the same challenges as unions in the new industrial landscape. Literature on employer associations' adaptive mechanisms highlights the need for employer bodies to manage the tension between offering traditional 'collective goods' while responding to the changing needs of individual members by offering tailored services for additional fees. We know that the provision of these individualised services creates competition between employer groups and professional services firms. But competition, resulting from regulatory changes, also occurs between associations themselves. This article explores such competition among Australia's three major national retail bodies. Product market competition between industry-based employer associations is rarely discussed in the literature and we aim to address this gap. We propose the following: (1) environmental variations arising from the aforesaid regulatory reforms serve to intensify industry association's product market competition; (2) environmental variations, however, also increase market segmentation between these associations, which dampens competition; (3) to the extent that the environmental changes affect the whole of the industry, these may prompt collaboration among industry bodies due to common interests between them, further reducing competitive pressure; (4) the history of relationship between competing associations may impact on their competitive dynamics; and finally, (5) intra-industry, product market competition tends to shift the organisational identity of an employer association away from a traditional and collective identity, towards a business-like identity.